Acute exacerbation of chronic Hepatitis B - Ning, Qin (Huazhong University of Science and Technology Press, 2019)
This book assembles recent achievements in both basic research and clinical management in the field of hepatology, virology and immunology. It provides up-to-date information for clinicians who can apply the relevant knowledge to their daily clinical practice and for researchers who are interested in clinically orientated studies. The updated and detailed technology, state-of-the-art treatment strategies provided in this book serve as references for clinicians and resident physicians in the daily management of ACLF. The rationality and strategies for basic research as well as patient management in this book can also be a valuable reference for other fatal and end stage liver diseases than HBV induced ACLF.